Pemanfaatan Sarana Pelayanan Kesehatan di Desa Sisarahiligamo Kecamatan Gunungsitoli Kota Gunungsitoli - Fitria, Dilla; Sulisna, Aida; Meliala, Sri Agustina (STIKES Yayasan RS.Dr.Soetomo, 2024)
Services in the health sector are a form of public service context and are absolutely implemented well by the government. Health facilities must be easily accessible to the community, especially by those who live in areas that are difficult to reach. Utilization of health services is the use of service facilities provided in the form of outpatient care, inpatient care, home visits by health workers or other forms of activities for the use of these services which are based on the availability and continuity of services, community acceptance, reasonableness, easily accessible to the community, affordable and quality. Many people in Indonesia still dont make good use of health facilities. Lack of knowledge about health facilities can be detrimental to people who need emergency treatment. The target of this activity is community in Sisarahiligamo Village, Gunungsitoli District, North Sumatra Province. The method in this activity is Providing education about the importance of health service facilities, Providing information about various types of health service facilities, Encouraging the public to visit health service facilities regularly, that will be socialized. The implementation of the activity was on May 17, 2024. As the result of this activity the community felt very useful for them.